Matrix eaudiobook A novel. - Groff, Lauren (Penguin Audio, 2021)
AN INSTANT NEW YORK TIMES BESTSELLER WINNER OF THE 2022 JOYCE CAROL OATES PRIZE FINALIST FOR THE 2021 NATIONAL BOOK AWARD FOR FICTION One of Barack Obama's Favorite Books of 2021 Named a Best Book of the Year by The New York Times , The Washington Post , TIME , NPR, The Financial Times , Good Housekeeping , Esquire , Vulture, Marie Claire , Vox, The Los Angeles Times, USA Today and more! “A relentless exhibition of Groff’s freakish talent. In just over 250 pages, she gives us a character study to rival Hilary Mantel’s Thomas Cromwell .” – USA Today “An electric reimagining . . . feminist, sensual . . . unforgettable.” – O, The Oprah Magazine “Thrilling and heartbreaking.” – Time Magazine “[A] page-by-page pleasure as we soar with her.” –New York Times One of our best American writers, and a uthor of the highly anticipated THE VASTER WILDS,  Lauren Groff returns with this exhilarating and groundbreaking novel Cast out of the royal court by Eleanor of Aquitaine, deemed too coarse and rough-hewn for marriage or courtly life, seventeen-year-old Marie de France is sent to England to be the new prioress of an impoverished abbey, its nuns on the brink of starvation and beset by disease. At first taken aback by the severity of her new life, Marie finds focus and love in collective life with her singular and mercurial sisters. In this crucible, Marie steadily supplants her desire for family, for her homeland, for the passions of her youth with something new to her: devotion to her sisters, and a conviction in her own divine visions. Marie, born the last in a long line of women warriors and crusaders, is determined to chart a bold new course for the women she now leads and protects. But in a world that is shifting and corroding in frightening ways, one that can never reconcile itself with her existence, will the sheer force of Marie’s vision be bulwark enough? Equally alive to the sacred and the profane, Matrix gathers currents of violence, sensuality, and religious ecstasy in a mesmerizing portrait of consuming passion, aberrant faith, and a woman that history moves both through and around. Lauren Groff’s new novel, her first since Fates and Furies , is a defiant and timely exploration of the raw power of female creativity in a corrupted world.